2022
DOI: 10.3390/ijms23126795
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Analysis and Functional Identification of Ancient Brassinosteroid Receptors in Ceratopteris richardii

Abstract: Phytohormones play an important role in the adaptive evolution of terrestrial plants. Brassinosteroids (BRs) are essential hormones that regulate multiple aspects of plant growth and development in angiosperms, but the presence of BR signaling in non-seed plants such as ferns remains unknown. Here, we found that BR promotes the growth of Ceratopteris richardii, while the synthetic inhibitor PCZ inhibits the growth. Using full-length transcriptome sequencing, we identified four BRI1-like receptors. By construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…In general, conserved residues are related to important functional roles; thereby a fixed substitution in a conserved residue always indicates functional residue migration or gain-of-function. With two gene-duplication events, a common ancestor of BR receptors diversified with BRL2 first, and then BRI1 separated with BRL1/3 [ 42 , 45 , 46 , 47 ]. Obviously, BRL2 possesses various amino acids at residue 597 (of AtBII1), suggesting that functional residue migration might have caused this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…In general, conserved residues are related to important functional roles; thereby a fixed substitution in a conserved residue always indicates functional residue migration or gain-of-function. With two gene-duplication events, a common ancestor of BR receptors diversified with BRL2 first, and then BRI1 separated with BRL1/3 [ 42 , 45 , 46 , 47 ]. Obviously, BRL2 possesses various amino acids at residue 597 (of AtBII1), suggesting that functional residue migration might have caused this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…In ferns, it is involved in the defence against biotic and abiotic stresses (Reynolds and John, 2004), and exhibits an apogamy-inducing function in C. richardii (Cordle et al, 2010). In the same fern species, other family of plant growth regulators, the brassinosteroids were documented to promote almost all fern growth and development processes (Zheng et al, 2022), being represented in our transcriptome list by many proteins, such as STEROL 1 (STE1). Regarding abscisic acid (ABA), which was assigned a vegetative growth inhibitory role in cultured D. affinis gametophytes (MenĂ©ndez et al, 2006), we found several associated proteins, such as the receptors GPCR-TYPE G PROTEIN 1 (GTG1) and PYR1-LIKE 5 (PYL5), the latter detected in the gametophyte of the fern Alsophila spinulosa (Hong et al 2022).…”
Section: 2 Organ Development and Plant Growth Regulators (Pgr)mentioning
confidence: 99%
“…This is rather surprising, since the continuously growing leaves of Welwitschia and the angiosperm-like leaves of Gnetum represent innovations that are extremely rare within gymnosperms. The long reproductive cycle of Welwitschia and Gnetum hinders their usefulness as models for reverse genetic approaches that have been successful in non-model, non-seed plants (Plackett et al, 2018;Zheng et al, 2022). On the other hand, Ephedra could be amenable as a model system for molecular developmental genetic studies, given their short reproductive cycles and relatively small genomes compared to other gymnosperms (Di Stilio and Ickert-Bond, 2021).…”
Section: Breaking the Branchesmentioning
confidence: 99%